Movement, Space, and Power in Cynewulf's Juliana. (2nd January 2020) - Williams, Kelly
ABSTRACT: Cynewulf's Juliana has long been the subject of feminist criticism, particularly focusing on the moments when Juliana claims power and agency in enclosure, even in her imprisonment. This article reevaluates Juliana's claims to power and agency from the perspective of modern critical theory and pragmatics, arguing that Juliana uses place-deixis to claim her body as a sovereign space, challenging the secular and political authority imposed upon her by her pagan father, her fiancé, and the emperor. These authorities force Juliana to move physically — first from her household, then to court, and then to different locations where she is tortured and imprisoned. However, her bodily movement contrasts not only with her spiritual fixity, but with her continuing sovereignty over the space of her body. Place-deixis and spatial imagery work with references to God's all-encompassing physical presence to redefine "power the relationship" and dwarf the limited authority that earthly authorities seem to wield.